Links Between Contexts and Middle to Late Childhood Social-Emotional Development. - Duong, Jeffrey; Bradshaw, Catherine P. (American Journal of Community Psychology, 2017)
Guided by the social-emotional learning (SEL) framework, we studied developmental trajectory patterns of five key competency outcomes spanning middle through late childhood: altruism, empathy, self-efficacy, aggression, and hyperactivity. We then assessed their links to middle childhood home, parental, and community contexts. Data from the Institute of Education Sciences' Social and Character Development Program, which comprised nearly 2,400 elementary school students who were followed from Grades 3 through 5, were analyzed using growth mixture modeling. Three trajectory groups emerged for each outcome, which were linked to childhood contexts. Positive parenting was associated with a lower likelihood of following a negative empathy trajectory among children. Neighborhood intergenerational closure promoted a stable self-efficacy trajectory. Residing in a high-risk community was linked to increasing normative beliefs about aggression. These findings suggest an important role of contexts in influencing childhood social-emotional development in the later elementary school years.